(untitled) (European Journal of Formal Sciences and Engineering, 2022)
The development of scientific knowledge and technology, including education have reached the 21st century. In this century, education is not only functioned to develop technology-based learning but also environment-based learning. To meet the challenge, some researchers concentrating on scientific education have developed and implemented local potency based science learning. The researchers systematically reviewed several literatures of relevant research and concluded that local potency based science learning has important roles in the 21st century learning. The learning is able to improve students’ abilities obligated by the 21st century learning that are: learning and innovation skills, digital literacy skills, and career and life skills.